Protection of forests from negative influences - Tashmatova Sh.R; Mirzaaliyev Saidkhan; Nabiyeva Manzura (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article will talk about the fact that the infestation of hidden foci of forest pests and diseases is among the most basic activities of the year, carried out through daily Entomological and Phytopathological observation, studies to identify them, as well as in the order of introduction of preventive measures.